Effects of different exercise prescription parameters on metabolic and inflammatory biomarkers in cancer patients: a systematic review, meta-analysis, and meta-regression - Wang, Jingyu; He, Yuxuan; Wang, Ziqian; Wang, Zhouluo; Miao, Yongqi; Choi, Jae-Young (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to systematically evaluate the effects of exercise interventions on metabolic and inflammatory biomarkers in cancer patients, and to identify potential dose–response relationships and modulatory mechanisms using Robust Variance Estimation (RVE) and MetaForest models.MethodsA systematic search of five databases was conducted from inception to March 6, 2025, based on the PICOS framework. Randomized controlled trials involving exercise interventions of ≥4 weeks in adults (≥18 years) with cancer were included. Effect sizes were pooled using RVE to estimate overall intervention effects. Risk of bias was assessed using the ROB2 tool, and the certainty of evidence was evaluated with the GRADE approach. Univariable RVE meta-regression was performed to examine the linear effects of each moderator. MetaForest was used to assess variable importance and to explore potential nonlinear relationships between moderators and intervention effects. Subgroup analyses were conducted by cancer type and intervention timing.ResultsA total of 83 eligible articles were included, representing 74 distinct randomized controlled trials, from which data were extracted. Exercise significantly reduced insulin levels (ES = –0.24, SE = 0.08, p < 0.01, I² = 49%), representing a small but meaningful effect. TNF-α showed a small effect (ES = –0.22, SE = 0.13) but was not statistically significant (p = 0.10, I² = 74%). MetaForest modeling revealed that the most favorable changes in IL-6, adiponectin, and IGF-1 were associated with high-intensity aerobic exercise; TNF-α, IL-8, and IL-10 responded best to longer weekly exercise duration; and improvements in glucose, leptin, and CRP were most pronounced when exercise was combined with caloric restriction.ConclusionRegular exercise confers modest but favorable effects on metabolic and inflammatory biomarkers in cancer patients. Meta-regression highlighted the importance of high-intensity aerobic exercise (HRR > 85%) in modulating IL-6, adiponectin, and IGF-1, as well as longer weekly exercise duration (>280 min/week) in improving TNF-α and IL-8. Mechanistically, high-intensity aerobic exercise may serve as a primary trigger for activating pathways that mediate metabolic and inflammatory improvements.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251002676.